The role of record management in promoting good corporate governance at the Road Traffic Training Academy in Gauteng Province, South Africa - Mokgehle, Rudolph Matlou (My University, 2025)
Record management has a very strong influence in determining as to whether organisations are doing what was supposed to be done, with requisite allocated resources, by following prescribed procedures and regulations in achieving their organisational mandate, thus governance. This study explored the role of record management in promoting good corporate governance at the Road Traffic Training Academy in Gauteng Province, South Africa, by adopting an exploratory research design based on the qualitative research approach. A non-probability purposive sampling was adopted to sample the whole population of 21 participants, comprising seventeen (17) Administrative staff dealing with records at RTTA and four (4) Unit Managers responsible for the four RTTA units. Semi-structured interviews were used to collect data, using an interview guide as a data collection tool, and 100% participation was secured. The collected data was analysed using thematic data analysis. The findings indicated that, record management at RTTA lacks systematisation, policy, procedures and proper training. Furthermore, the study revealed that RTTA’s functions rely heavily on good stakeholder engagement, sustained by the provision of records for accountability and transparency to prove good corporate governance. The study revealed RTTA records management challenges such as a lack of professional records practitioners, haphazard records management systems, loss and misplacement of records, lack of record management training programmes, poor management support for record management programmes; and lack of formalised systems such as policies and regulations. Thus, it hampers good corporate governance. Possible solutions suggested were that record management systems such as filling plans, records appraisal, and disposal schedules. Thus, amongst other recommendations, the study provided that the record management practices at RTTA adhere to the legislative frameworks that govern record management in South Africa, as well as observing the international best practices.
Thesis (M. (Information Studies)) -- University of Limpopo, 2024
Keywords: Road Traffic Training Academy; RTMC; Records management; Corporate governance; Accountability; Transparency; Auditing; Gauteng Province; South Africa; Records -- Management; Corporate governance; Auditing